1997
DOI: 10.1002/hep.510250233
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Type 2–Like T–Helper Cells in Hepatitis C Virus Infection: Implications for Hepatitis C Virus Chronicity

Abstract: One striking clinical feature of hepatitis C virus (HCV) infection is that more than 50% of patients with acute hepatitis C will develop chronic infection. To investigate its possible mechanisms, we examined the activation of type 2‐like T‐helper (Th2‐like) cells relating to the development of chronicity. Peripheral blood CD4+ T‐cell proliferation and cytokine secretion in response to a panel of recombinant HCV antigens including core (C22), envelope 1 (E1), E2, nonstructural (NS) protein 4 (C100), fusion prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
174
4

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(186 citation statements)
references
References 63 publications
8
174
4
Order By: Relevance
“…Measurement of cytokine levels in the sera of subjects with chronic HCV has provided inconsistent results, with some studies finding increased levels of IFN-g and IL-2 [159], and others a prominent increase in IL-4 and IL-10 [160], compared to healthy control subjects. Cytokine production from PBMC stimulated with HCV proteins demonstrated significantly higher levels of IFN-g and IL-2 in those that had previously cleared infection, while patients with chronic HCV had increased IL-4 and IL-10 production [161]. Evidence for interference in the CD4+ T cell priming environment in acute HCV infection, resulting in reduced effectiveness of the integrated CD4+ and CD8+ adaptive immune response, has been provided by examination of purified HCV-specific, central memory (CCR7+) CD8+ T cells from subjects with acute HCV [162].…”
Section: Interactions Between Cd4+ and Cd8+ T Cellsmentioning
confidence: 96%
See 1 more Smart Citation
“…Measurement of cytokine levels in the sera of subjects with chronic HCV has provided inconsistent results, with some studies finding increased levels of IFN-g and IL-2 [159], and others a prominent increase in IL-4 and IL-10 [160], compared to healthy control subjects. Cytokine production from PBMC stimulated with HCV proteins demonstrated significantly higher levels of IFN-g and IL-2 in those that had previously cleared infection, while patients with chronic HCV had increased IL-4 and IL-10 production [161]. Evidence for interference in the CD4+ T cell priming environment in acute HCV infection, resulting in reduced effectiveness of the integrated CD4+ and CD8+ adaptive immune response, has been provided by examination of purified HCV-specific, central memory (CCR7+) CD8+ T cells from subjects with acute HCV [162].…”
Section: Interactions Between Cd4+ and Cd8+ T Cellsmentioning
confidence: 96%
“…Similarly, the ratio of IgG2 to IgG1 antibodies against core and NS5 was greater than 1.0 in those who cleared infection, whereas it was less than one for all antigens in those with chronic infection. This IgG2 predominance has been linked to a Th1 bias in CD4 T cell responses and may be associated with viral clearance [166]. Evidence for the notion that rapid development of an effective humoral response before the emergence of potential viral escape mutations may contribute to viral clearance has been provided by detection of a higher anti-HCVantibody titer in the first two months of infection in chimpanzees who go on to clear infection [116].…”
Section: Humoral Immune Responsesmentioning
confidence: 98%
“…We speculated that the Th1-dominant immunological response, inherent in sarcoidosis, resulted in an attack against the hepatocytes infected with HCV, which increase in number during steroid therapy. 7 In our patient, because it was clinically confirmed that the activity of sarcoidosis was sufficiently controlled by the steroid therapy, she was treated with IFN for the chronic active hepatitis C. We were greatly concerned about a possible reactivation of sarcoidosis by the IFN therapy. Nakajima et al 8 have recently reported a patient with sarcoidosis in remission who had recurrent sarcoidosis after a 5-month course of IFN-α for chronic hepatitis C. Fortunately, during the IFN therapy, no evidence of the reactivation of sarcoidosis was noted in our patient, who was maintained with a low dose of prednisolone.…”
Section: Discussionmentioning
confidence: 90%
“…25 A similar cytokine evolution has been reported in a patient with acute hepatitis C that progressed to chronic hepatitis. 26 Treatment with IFN-α rapidly decreased the serum concentration of IL-8, and that of a Th 2 cytokine, IL-10, in our patient. In contrast, serum concentrations of TNF-α and both sTNFR-p55 and sTNFR-p75 decreased gradually, while remaining elevated during IFN treatment.…”
Section: Discussionmentioning
confidence: 93%